Pelatihan Lesson Study sebagai Peningkatan Profesionalisme Guru SMK Widya Yahya - Pramono, Arief; Rozanna, Mira; Septiana, Dian; Jaya, Ida (Jurnal Pemberdayaan Ekonomi, 2025)
Purpose: This program aims to enhance teacher professionalism at SMK Widya Yahya by improving understanding of student learning and teaching practices, generating useful instructional outcomes, promoting systematic improvement through collaborative inquiry, and fostering pedagogical knowledge exchange. Methodology/approach: The program used lectures, discussions, Q&A, and macro teaching within a PDCA-based lesson study involving collaborative planning, open-class observation, reflection, and follow-up. It was held on March 17, 2020, with 20 SMK Widya Yahya teachers in Pringsewu Regency. Results/findings: Participants gained a better understanding of lesson study and applied it in their teaching, fostering collaboration, reflection, and feedback, while enhancing student-centered strategies, lesson plan quality, and classroom management. Conclutions: Lesson study training effectively enhanced teacher professionalism at SMK Widya Yahya by fostering collaborative learning communities and continuous improvement in instructional quality. The PDCA-based implementation proved suitable for promoting reflective teaching practices and student-centered learning. Limitations: The program was limited to a single school and a small number of participants, which may restrict the generalizability of the results. Long-term impact on student learning outcomes was not measured within the program’s timeframe. Contribution: This program contributes to the development of teacher competencies through sustained, collaborative professional development. It also provides a replicable model for implementing lesson study in vocational school contexts in Indonesia.